Carbon nanotube dielectrophoresis: Theory and applications. Issue 21 (22nd June 2020) - Rabbani, Mohammad Towshif; Sonker, Mukul; Ros, Alexandra
Abstract: Carbon nanotubes (CNTs) are one of the most extensively studied nanomaterials in the 21st century. Since their discovery in 1991, many studies have been reported advancing our knowledge in terms of their structure, properties, synthesis, and applications. CNTs exhibit unique electrothermal and conductive properties which, combined with their mechanical strength, have led to tremendous attention of CNTs as a nanoscale material in the past two decades. To introduce the various types of CNTs, we first provide basic information on their structure followed by some intriguing properties and a brief overview of synthesis methods. Although impressive advances have been demonstrated with CNTs, critical applications require purification, positioning, and separation to yield desired properties and functional elements. Here, we review a versatile technique to manipulate CNTs based on their dielectric properties, namely dielectrophoresis (DEP). A detailed discussion on the DEP aspects of CNTs including the theory and various technical microfluidic realizations is provided. Various advancements in DEP‐based manipulations of single‐walled and multiwalled CNTs are also discussed with special emphasis on applications involving separation, purification, sensing, and nanofabrication.